2016
DOI: 10.1007/s11695-016-2503-7
|View full text |Cite
|
Sign up to set email alerts
|

The Peri-operative Bariatric Surgery Care in the Middle East Region

Abstract: The wide variation in the peri-operative care of bariatric surgery in the Middle East region highlights the need for regional guidelines based on international guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 35 publications
0
13
0
1
Order By: Relevance
“…referral to dietitian, smoking cessation, referral to psychologist, screening for obstructive sleep apnea, colonoscopy screening and cardiologist referral for patients above 50 years, drain and urinary catheter placement, leak test, thromboembolism prophylaxis, and vitamin supplementation). (50) A survey of IFSO-MENA surgeon members documented that 65% of 148 respondents did not perform routine pre-operative endoscopy for patients undergoing one anastomosis gastric bypass. (51) Retrospective studies have suggested that routine esophagogastroduodenoscopy (EGD) can be informative in preventing the cancellation or postponement of bariatric surgery in the UAE (52) and KSA, (53) whereas other studies showed no benefit in surgical management in Qatar (54) and among individuals without symptoms of gastroesophageal reflux disease in Jordan.…”
Section: Preoperative Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…referral to dietitian, smoking cessation, referral to psychologist, screening for obstructive sleep apnea, colonoscopy screening and cardiologist referral for patients above 50 years, drain and urinary catheter placement, leak test, thromboembolism prophylaxis, and vitamin supplementation). (50) A survey of IFSO-MENA surgeon members documented that 65% of 148 respondents did not perform routine pre-operative endoscopy for patients undergoing one anastomosis gastric bypass. (51) Retrospective studies have suggested that routine esophagogastroduodenoscopy (EGD) can be informative in preventing the cancellation or postponement of bariatric surgery in the UAE (52) and KSA, (53) whereas other studies showed no benefit in surgical management in Qatar (54) and among individuals without symptoms of gastroesophageal reflux disease in Jordan.…”
Section: Preoperative Practicesmentioning
confidence: 99%
“…Some low-income MENA countries may not have any access to bariatric surgery or may be lacking comprehensive bariatric programs. (50) Published reports document varied patient outcomes of bariatric surgery in the MENA region in adults (57,58) and youth. (59,60) However, a literature review (61) noted relatively few publications on bariatric surgery in the Arabic peninsular countries as compared to western regions and called for the creation of a regional registry.…”
Section: Healthcare Accessmentioning
confidence: 99%
“…The survey was uploaded to Survey Monkey, a link was sent to the PASMBS social media platforms and to all members of the PASMBS Telegram group in 2017 as described previously [7]. Frequent reminders were sent to the Telegram group and via social Media platforms.…”
Section: Check For Updatesmentioning
confidence: 99%
“…The aim of this survey is to study the incidence of VTE and the practice of VTE thromboprophylaxis in the Middle East region represented by members of the Pan Arab Society of Metabolic and Bariatric Surgery (PASMBS). PASMBS includes surgeons from the Middle East and Africa (full description of the PASMBS group was provided in an earlier publication by Nimeri, et al) [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, this number proved to have increased by 2.5-fold between the years 2011-2014 (6,7). This increase was especially noted in the Middle Eastern countries due to the increased burden of obesity, diabetes and metabolic syndrome they are facing there as of recent years (8). Currently, more than 30% of the population in the gulf region demonstrate a body mass index (BMI) exceeding 30, with Kuwait having 39.7% of its population placed in this obesity range (9).…”
Section: Introductionmentioning
confidence: 99%